Komunikasi Persuasif Pimpinan Terhadap Peningkatan Prestasi Mahasiswa - Fatimah Zahra; Riswanto (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2025)
This study aims to examine the influence of persuasive leadership communication on improving student achievement in higher education. Based on the hypothesis regarding the effect of persuasive leadership communication on student achievement, the F-test results indicate that the regression model is statistically significant simultaneously, with an F value of 49.901 and a significance level of 0.000 (p < 0.05). Partially, the t-test results show that openness (t = 2.516; p = 0.013), support (t = 2.908; p = 0.004), positive attitude (t = 3.926; p = 0.000), and equality (t = 2.254; p = 0.026) have a significant influence on student achievement. In contrast, empathy does not have a statistically significant effect (t = 1.690; p = 0.093). The most dominant dimension is a positive attitude, with the highest beta coefficient (? = 0.259).This research employed a quantitative method involving 150 students from the Faculty of Social and Political Sciences at Universitas Muhammadiyah Bengkulu, using a Likert-scale-based questionnaire. Data analysis was carried out using descriptive statistics, Pearson correlation, and multiple linear regression via SPSS. The findings highlight the importance of leadership communication strategies that are open, supportive, positive, and egalitarian in building an academic environment that fosters and motivates student achievement. This study contributes both theoretically and practically to the development of leadership communication in higher education institutions.